Metabolic syndrome among non-obese adults in the teaching profession in Melaka, Malaysia - Lee, S.C.; Hairi, N.N.; Moy, F.M. (Japan Epidemiological Association, 2017)
Background: Non-obese individuals could have metabolic disorders that are typically associated with elevated body mass index (BMI), placing them at elevated risk for chronic diseases. This study aimed to describe the prevalence and distribution of metabolically obese, non-obese (MONO) individuals in Malaysia. Methods: We conducted a cross-sectional study involving teachers recruited via multi-stage sampling from the state of Melaka, Malaysia. MONO was defined as individuals with BMI 18.5-29.9 kg/m2 and metabolic syndrome. Metabolic syndrome was diagnosed based on the Harmonization criteria. Participants completed self-reported questionnaires that assessed alcohol intake, sleep duration, smoking, physical activity, and fruit and vegetable consumption. Results: A total of 1168 teachers were included in the analysis. The prevalence of MONO was 17.7% (95% confidence interval [CI], 15.3-20.4). Prevalence of metabolic syndrome among the normal weight and overweight participants was 8.3% (95% CI, 5.8-11.8) and 29.9% (95% CI, 26.3-33.7), respectively. MONO prevalence was higher among males, Indians, and older participants and inversely associated with sleep duration. Metabolic syndrome was also more prevalent among those with central obesity, regardless of whether they were normal or overweight. The odds of metabolic syndrome increased exponentially from 1.9 (for those with BMI 23.0-24.9 kg/m2) to 11.5 (for those with BMI 27.5-29.9 kg/m2) compared to those with BMI 18.5-22.9 kg/m2 after adjustment for confounders. Conclusions: The prevalence of MONO was high, and participants with BMI ≥23.0 kg/m2 had significantly higher odds of metabolic syndrome. Healthcare professionals and physicians should start to screen nonobese individuals for metabolic risk factors to facilitate early targeted intervention.